UU KETERBUKAAN INFORMASI PUBLIK ANTARA HARAPAN DAN KENYATAAN - Suko Widodo (Universitas Muhammadiyah Sidoarjo, 2013)
Disclosure of public information is one manifestation of the implementation of good governance where the public information disclosure is the duty of government and public institutions. It refers to the fact that the public information is public property and is not owned by the government and public institutions. Therefore, to be able to meet these conditions, the Freedom of Information Law was established, despite the fact that the law is not so popular in the community, so it is still necessary